Churg-Strauss Syndrome associated with montelukast: Three Case Reports - Fatih Yildiz; Suzan Zorludemir; Eren Erken (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2014)
Churg-Strauss syndrome (new name Eosinophilic granulomatosis and polyangiitis); asthma, fever, peripheral blood eosinophilia, eosinophilic tissue infiltration, small and medium sized arteries characterized by necrotizing granulomatous inflammation is a multisystemic disorder. Classified in ANCA associated vasculitis. The drugs such as leukotriene receptor antagonists (montelukast, zafirlukast, pranlukast), inhaled glucocorticoids, omalizumab, cocaine and clarithromycin is thought to be associated with Churg-Strauss Syndrome cases have been reported. Herein we presented a rare three CSS cases associated with montelukast. [Cukurova Med J 2014; 39(2.000): 347-352]